Analisis Perubahan Tutupan Lahan Pertanian dan Perkebunan di Bendungan Gondang, Kabupaten Karanganyar menggunakan Google Earth - Purwanti, Renita; Setyanto, Yogyrema; Wibowo, Adi (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
The construction of a dam generally aims to mitigate against floods, management of water availability, irrigation for agriculture, and also one of the tourism attractions. The construction of the dam has implications for land use change around the dam area which causes changes in land cover. The Gondang Dam is one of the government programs that began to be built in 2014 where the rehabilitation of the irrigation channels was completed in 2019 and has reached the maximum storage capacity in 2020. This study aims to analyze changes in agricultural and plantation land cover before and after the Gondang Dam was built using Imagery Satellites sourced from Google Earth are multitemporal with acquisition years 2013 and 2022. Land cover data was obtained through the on screen digitization method by producing 12 land cover classes and analyzed using the overlay method using a Geographic Information System (GIS). The overall accuracy test results for land cover data for 2013 and 2022 are 94.33% and 96.83%, respectively. The biggest change in land cover occurred in the plantation land cover class which experienced a decrease in area of 29.72 Ha